Biomass : to win the future - Shi, Yuanchun (Lexington Books, 2013)
Biomass, translated into English for the first time, introduced the world to China's development of bioenergy in the turn of the 21st century and proposed further development of bioenergy as well. Businessmen, scientists, and technicians alike who are interested in bioenergy will find a great deal of information within this book.